Bikes and Bloomers - Jungnickel, Kat; Dent, Liberty (Goldsmiths Press, 2023)
The bicycle in Victorian Britain is often celebrated as a vehicle of women's liberation. But much less is known about another critical technology with which women forged new and mobile public lives – cycle wear. Despite its benefits, cycling was a material and ideological minefield for women. Conventional fashions were vastly inappropriate, with skirts catching in wheels and tangling in pedals. Yet wearing more identifiable ‘rational’ cycle wear could elicit verbal and sometimes physical abuse from parts of society threatened by newly mobile women.